PELATIHAN PEMBUATAN SABUN CUCI TANGAN PROBIOTIK FERMENTASI KOMBUCHA BUNGA TELANG KEPADA MAHASISWA FARMASI SMESTER 5 UNIVERSITAS MATHLA’UL ANWAR BANTEN SEBAGAI PENINGKATAN WAWASAN DALAM MATA KULIAH BIOTEKNOLOGI - Nurullah Asep Abdilah; Firman Rezaldi; M. Fariz Fadillah; Mu’jijah Mu’jijah; Usman Setiawan; Swastika Oktavia; Meliyawati Meliyawati; Fernanda Desmak Pertiwi (Pusat Riset dan Inovasi Nasional, 2022)
Telang flower kombucha is a probiotic that has the potential to be developed as a functional drink and even an active cosmetic ingredient in the form of hand soap as an effort to break the chain of transmission of COVID-19 and its mutations. The purpose of this activity is to provide additional insight to students, especially in the pharmaceutical study program at the Faculty of Health Pharmacy, Mathla'ul Anwar University, Banten, in utilizing the fermented kombucha solution of telang flower as an active ingredient in environmentally friendly hand soap cosmetics. The results of the activity showed that the service participants had increased knowledge or insight about the importance of using conventional biotechnology products as a new breakthrough in the pharmaceutical field. This can be seen from the increase in the pre-test and post-test which have been conveyed a lot during material exposure during pharmaceutical biotechnology lectures and during training. Participants who have attended training on making probiotic handwashing soap from fermented kombucha flower telang solution are more enthusiastic and understand the importance of the benefits of fermenting kombucha flower telang not only in the functional food sector but also in the potential for environmentally friendly cosmetics.